Designing a developmental progression to assess students' conceptual understandings by focusing on the language demands in Science. Issue 3 (November 2021) - Panizzon, Debra; Pegg, John; Arthur, Dagmar; McCloughan, Gerry
Few would argue the value of learning progressions in providing useful structures for selecting and sequencing in a developmental manner the key components of an 'intended curriculum'. Yet, there are pervading issues around what is meant by a developmental sequence, along with how they are used to assess what learners know, understand and can do. One key oversight in Science is recognising the role of technical and non-technical language in student conceptual development. This article reports on the construction of a hypothesised learning progression that identifies students' progress in understanding essential concepts in the Chemical Sciences from Foundation to Year 6. It is based upon an extensive analysis of the technical and non-technical language of the Australian Curriculum: Science. The progression was constructed by focusing upon learner-appropriate language and scientific understanding with the Structure of the Observed Learning Outcome model (Pegg, 2018 ) providing the theoretical basis for ensuring systematic and objective rigour in the resultant developmental progression.